A repository of recovered materials from post-earthquake reconstruction areas - Angelucci, Filippo; Cellucci, Cristiana; Di Sivo, Michele; Ladiana, Daniela (TECHNE - Journal of Technology for Architecture and Environment, 2018)
Following the series of ‘severe’ seismic events that began in 2009, Italian legislation classified demolition debris as urban waste, despite Directive 2008\98calling for the reuse/recycling of 70% of all waste from human activities by 2020. This choice will produce a technical, cultural, environmental and economic impoverishment in territories already under heavy strain. Considering the convergence between the paradigms of the Circular Economy and Smartness, the essay identifies possible technological innovations for creating repositories of recovered materials. Collective activities and spatialities tied to processes of selection, reuse and recycling can generate forms of social-organisational-collective resilience required to confront the losses and damages suffered by a community.